Fertility trends and net reproduction in Agincourt, rural South Africa, 1992-2004 - GARENNE, MICHEL L. (2007)
AIMS: To analyse trends in fertility rates and net reproduction rates in Agincourt, a rural area of South Africa located in the former homeland of Gazankulu near the Mozambican border. Trends are analysed in the context of widely available modern contraceptive methods and increasing HIV/AIDS. METHODS: A health and demographic surveillance system has been in place since 1992, covering a population of approximately 70,000 persons, with an annual census update and comprehensive recording of births and deaths. It was complemented by a retrospective study of fertility at baseline. Retrospective and prospective data were used to calculate trends in fertility, survival, and net reproduction. When possible, they were compared with data from other censuses and surveys in the same ethnic group. RESULTS: The fertility transition has almost ended over a course of 25 years in Agincourt. The total fertility rate (TFR) averaged 6.0 in 1979 and 2.3 in 2004. Fertility declined in proportionate fashion in all age groups including adolescents in the recent period. The net reproduction rate (NRR) declined from 1.8 to 1.0 during the prospective period (1992–2004). At current rates of change in fertility and mortality, the NRR can be expected to reach 0.63 by the year 2010. CONCLUSIONS: The situation of a below-replacement fertility level is new for rural Africa, and is likely to have many demographic, economic and social implications. The population could decline in the country as a whole, and is nearly static in Agincourt because of negative migration flows balancing the small excess from natural increase.